Design optimisation for stent manufacture - Khan, Muhammad Farhan (2018)
Intravascular stents of various designs are currently used to prop open diseased arteries and there is evidence that different stent geometries have different in-stent restenosis rates. The majority of commercially available stents are designed generically to fit all individuals. Recent advances in imaging and catheter technologies, however, allow measurement of lesion shape and stiffness. Incorporating patient specific data into the stent design process could enable the development of customised stents. Considering the variety of lesion types, it is envisaged that better outcomes will be achieved if a stent is custom designed in such a way that it has variable radial stiffness longitudinally to hold the varying pressure of plaque and healthy artery at the same time while maintaining an acceptable lumen diameter. This type of operation is suitable for topology optimisation potentially allowing for optimal material distribution of a stent. The primary aim of this research is to develop new stent designs for a set of plaque types and investigate the final radius of the lumen after stent implantation. Stent geometries were obtained by topology optimisation for minimised compliance under different stenosis levels and plaque materials. Three types of stenosis levels by area, i.e. 30%, 40% and 50% with each type having three different plaque material properties i.e. calcified, cellular and hypocellular were studied. The optimisation results were transformed to clear design concepts and their performance was evaluated by implanting them in their respective stenosed artery types using finite element analysis. The results were compared with a generic stent in similar arteries, which showed that the new designs showed less recoil. In the hardest (calcified) of plaques studied, topology optimised designs overall resulted in 2%, 2% and 6% residual area stenosis compared to 10%, 29% and 35% from the generic design in arteries with 30%, 40% and 50% stenosis respectively. It was shown that higher material distribution resulted in the central region of the stent in order to resist implantation recoil due to higher plaque compressive loads. Additive manufacturing (AM) was utilised to validate the computational approach used in this thesis. This work provides a proof of concept for stents tailored to specific lesions in order to minimise recoil and maintain a patent lumen in stenotic arteries.